Lingnan University Education and Academic Research from a Library Perspective - ZHOU Yi, SU Rina, (Journal of Research for Christianity in China (JRCC), 2025)
From the perspective of library collection, with the newly excavated historical materials such as primary archives, this paper analyzes the concept, teaching policy and academic research of Lingnan University by combing and analyzing the library collection policy, characteristic collection and source. Guangzhou Lingnan University is a Christian University initiated by the Christian community at home and abroad in Guangzhou, which was unique in that she was the only one of the 13 Christian Protestant universities in China that did not belong to any denominational and organizational school, and Its quality of teaching and academic research has been at the forefront of the national universities. In 1945 the joint board of directors of New York Christian University developed China's post-war rehabilitation Christianity program, which includes intending to divide the existing university into two classes, Lingnan University was included in the first class. Due to its unique school background and school-running philosophy, Lingnan University has consistently focused on Chinese society, especially on the local culture of Guangdong society, in teaching policy and academic research. In the teaching of business and agriculture, Lingnan University also pays more attention to the actual situation in Guangdong and even China, so that graduates can meet the needs of Chinese society; in the aspect of academic research, Lingnan University’s carried out "Guangdong Document Arrangement and Excavation", the Southwest Social Survey and the "China Research" project have distinctive Lingnan characteristics, especially the "China Research" have the modern academic research breath, since not only the research content and the topic angle is very novel, but also make great use of the western modern academic research methods, and it carries out research on Chinese, especially Lingnan area’s history, culture and society from the perspective of sociology, anthropology, economics and cultural exchange between China and the West since the Qing Dynasty. The analysis of the collections of Lingnan University Library and of the educational and academic research under the view of book collection can reveal the origin, development and changes of Lingnan University from a glimpse of the collision, conflict, blending and integration of the Chinese and Western Cultures in Lingnan University and Christian Education.